The Gambia : 2006 Article IV Consultation and Assessment of Performance Under the Staff-Monitored Program-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report, 2006)
The authorities' response to policy recommendations in the 2005 Article IV Consultation has been generally positive, and authorities successfully completed an SMP. The appreciation reflects the tightening of monetary policy and increased inflows of remittances, transfers, and FDI. The Gambian economy has stayed relatively competitive. The principal purpose of the SMP was to help the authorities reestablish a policy track record. In particular, over commitments, expenditure overruns, and extrabudgetary expenditures risk further accumulation of domestic arrears and/or increased domestic borrowing.